Student Satisfaction and Learning Outcomes during Online Course Delivery - A Case Study - Baca Eleonora (Ovidius University Annals: Economic Sciences Series, 2021)
The paper presents the results of a study on students’ satisfaction concerning online teaching in general and ESP (English for Special Purposes) in particular, considering the implications of an unprecedented shift in education, a turn from the traditional face-to -face system to an emergency remote online learning, imposed by the restrictions of the COVID-19 pandemic in Romania. The results reveal a general positive attitude towards the efforts made by the teaching staff during online teaching; therefore, we are confident that the less encouraging aspects revealed by the study can be adjusted in time and improved to better suit and serve the needs of our students.